Phytomolecules-Coated NiO Nanoparticles Synthesis Using Abutilon indicum Leaf Extract: Antioxidant, Antibacterial, and Anticancer Activities - Khan SA (Dove Medical Press, 2021)
Shakeel Ahmad Khan,1 Sammia Shahid,2 Amber Ayaz,2 Jawaher Alkahtani,3 Mohamed S Elshikh,3 Tauheeda Riaz4 1Center of Super-Diamond and Advanced Films (COSDAF) and Department of Chemistry, City University of Hong Kong, Kowloon, 999077, Hong Kong; 2Department of Chemistry, School of Science, University of Management and Technology, Lahore, 54770, Pakistan; 3Department of Botany and Microbiology, College of Science, King Saud University, Riyadh, 11451, Saudi Arabia; 4Department of Chemistry, Government College Women University Sialkot, Sialkot, PakistanCorrespondence: Shakeel Ahmad Khan Email shakilahmad56@gmail.comBackground: NiO nanoparticles have attracted much attention due to their unique properties. They have been synthesized using chemical and physical techniques that often need toxic chemicals. These toxic chemicals cannot easily be removed from the nanoparticle’s surface, make them less biocompatible, and limit their biological applications. Instead, plants based green synthesis of nanoparticles uses phytomolecules as reducing and capping agents. These phytomolecules are biologically active with no or less toxic effects.Materials and Methods: Phytomolecules-coated NiO nanoparticles were synthesized employing a green route using Abutilon indicum leaf extract. For comparative study, we also have synthesized NiO nanoparticles using the co-precipitation method. Synthesized nanoparticles were successfully characterized using different spectroscopic techniques. The synthesized nanoparticles were evaluated for antibacterial activity with agar well diffusion assay against different bacteria compared to standard drug and plant extract. They are also examined for anticancer potential using MTT assay against HeLa cancer cells, and further, their antioxidant potential was determined using DPPH assay. Biocompatibility of the synthesized nanoparticles was assessed against fibroblast cells.Results: Phytomolecules-coated NiO nanoparticles were demonstrated superior antibacterial and anticancer performance against bacteria (E. coli, B. bronchiseptica, B. subtilis, and S. aureus) by presenting highest zone of inhibitions (18 ± 0.58 mm, 21 ± 0.45 mm, 22 ± 0.32 mm, and 23 ± 0.77 mm) and HeLa cancer cells by exhibiting the least cell viability percentage (51.74 ± 0.35%) compared to plant extract and chemically synthesized NiO nanoparticles but were comparable to standard antibiotic and anticancer drugs, respectively. Phytomolecules-coated NiO nanoparticles were also demonstrated excellent antioxidant activity (79.87 ± 0.43% DPPH inhibition) and biocompatibility (> 90% cell viability) with fibroblast cells.Conclusion: Nanoparticle synthesis using the Abutilon indicum leaf extract is an efficient and economical method, produces biocompatible and more biologically active nanoparticles, which can be an excellent candidate for therapeutic applications.Keywords: NiO nanoparticles, green synthesis, A. indicum, biological, anticancer, antibacterial